Error Analysis of a Sample of Kuala Kangsar University Students’ English Placement Writing Test - Shamimah Mohideen (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2023)
Error analysis is a linguistic analysis that focuses on identifying and describing the learner’s error in target language learning. This study focuses on grammatical mistakes frequently made by students who took their English placement test after enrolment at Universiti Sultan Azlan Shah. Samples from the writing test were collected. The errors were identified, recorded, categorized and analyzed. The findings of this study shed light on the most frequently occurring types of mistakes made by a sample of Malaysian ESL learners of higher learning institutions. From this, the researcher can determine the learners’ problem areas. It is found that the most frequently occurring grammatical errors are errors in the inflexion of verbs according to tense and number. Students also made mistakes using the past participle for the perfect tenses and passive sentences. Many of these errors were mainly technical, which did not affect the intended meanings. These errors reveal Malaysian students' difficulties in mastering the English verb forms due to the significant differences between the Malay and English verb systems. To a certain extent, participants are influenced by their native language structure and transfer them when using the L2. Lack of familiarity with exposure and usage of the target language can be attributed to the errors. Frequently occurring mistakes need to be treated with the necessary intervention by instructors, and suitable learning strategies need to be practised by students to prevent fossilization.